Status of Natural Regeneration in Tropical Forests of the Andaman Islands - Elkunchwar, Satish; Savant, P. V.; Rai, S. N. (Indian Forester, 1997)
The Tropical Evergreen Forests are highly sensitive to disturbance in the original crop composition under natural environment. Proper manipulation of canopy and judicious application of silvicultural systems may maintain the balanced composition. The regeneration survey revealed that though the regeneration status as such is satisfactory in the tropical forests of Andamans, change in stocking under the present management practices indicate decline of ornamental and softwood species in some Forest Divisions and fall in ply species in some localities. A conservative approach in exploitation schedule and improving future crop by adequate regeneration of desired species compatible to ecosystem needs should be adopted in such areas. Overall position of total seedlings per ha shows marginal improvement in worked areas than in unworked areas, most of Which are from miscellaneous category. Although the silvicultural system practised in Andaman forests primarily aims at conversion to uniform crop by few identified economic tree species it is more than four decades old and hence the system needs immediate critical review in the context of ground reality obtained thereon.